Preposing and Postposing in English and Arabic: A Contrastive Study - Saad, Israa Talib (Journal of Humanities & Social Sciences, 2018)
Preposing and postposing are interesting linguistic phenomena that endow English and Arabic fascinating means of expression and variation. They involve a number of devices that bring certain elements into focus by moving them either into sentence initial (preposing) or final (postposing) position. In Arabic, these two phenomena are treated together under one heading known as ‘preposing and postposing’ which is part of a wider linguistic phenomenon known as ‘al-udul’. By shifting certain elements from their normal positions, certain linguistic and aesthetic purposes and benefits are attained. The study aims at shedding some light on the processes involved within these phenomena in both English and Arabic to show how each language deals with (and considers) them, what types of shifts associated with these phenomena in the two languages and which language makes greater uses of ‘preposing and postposing’ and why. It has been concluded that in spite of the fact that in both languages preposing and postposing are used to present information by applying different word orders in order to highlight different aspects of meaning, the issue of considering and discussing them in English and Arabic differs considerably.
Keywords: Preposing; postposing; word order; norms; shift; violations